Diversity and structure preferences for ant-hemipteran mutualisms in cocoa trees (Theobroma cacao L., Sterculiaceae) - Koch, Elmo Borges de Azevedo; Marques, Thamy E. D.; Mariano, Cléa S. F.; Neto, Esperidião A. S.; Arnhold, Alexandre; Peronti, Ana L. B. G.; Delabie, Jacques H. C. (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2020)
The aim of this study is to evaluate the diversity and specificity of ant-hemipteran mutualisms according to the different structures observed on cocoa trees. The experiment was carried out in two cocoa planting systems: cabruca and derruba total at Ilhéus, Brazil. We made observations and collected monthly over one year the mutualistic ants and hemipterans that occurred on Theobroma cacao L. trees. Observations were performed on cacao trees at three distinct sites of the plant: flowers, pods and leaf flush. We observed 932 ant-hemipteran associations, comprising 203 different mutualistic interactions. The assemblage was composed of 26 hemipteran species and 54 ant species. No differences were observed in the ant community, however, we found differences in the hemipteran community according to the different structure evaluated. We recorded a total of 404 trophobiosis events on pods, 394 on leaf flushes and 134 on flowers. Our results point out the diversity of ant-hemipteran trophobioses in the cocoa agrosystems resembles the diversity found in tropical forests and demonstrate that the location of interactions may result in ecological restrictions for some organisms involved in these trophobioses in cacao agrosystems.
Keywords: Formicidae; Hemiptera; Trophobioses; Theobroma cacao; Insect-insect relationships